Impact Of Situation, Organization Culture, And Mental Characteristics On The Migration Effectiveness Of Knowledge Sharing In Chinese-Foreign Cooperative Schools In Higher Education In Guangdong - Xiong, Xiaofang (Migration Letters, 2024)
This study aims to study the levels of situation, organization culture and mental characteristics, and the effectiveness of knowledge sharing in Chinese-foreign cooperative schools in higher education ;to identify the impact of situation, organization culture, and mental characteristics on the effectiveness of knowledge sharing in Chinese-foreign cooperative schools in higher education;to develop a model for increasing the effectiveness of knowledge sharing in Chinese-foreign cooperative schools in higher education. The research design employs both qualitative and quantitative methods to achieve the objectives and test the hypotheses. Questionnaires were distributed to teachers in Chinese-foreign cooperative universities, and participants were selected based on expertise, availability, convenience, and interest. Confirmatory factor analysis was used to test convergent and discriminant validity. The study focused on the situation, organization culture, mental characteristics, and effectiveness of knowledge sharing in Chinese-foreign cooperative schools in Guangdong Province, China. Confirmatory factor analysis was employed to test whether a factor and its observed variables conform to the theoretical relationships posited by the researchers. According to the hypothesis, the impact of situation on the effectiveness of knowledge sharing in Chinese-foreign cooperative universities was statistically significant. The influence of organization culture on the effectiveness of knowledge sharing in Chinese-foreign cooperative universities was statistically significant. The impact of mental characteristics on the effectiveness of knowledge sharing in Chinese-foreign cooperative universities was statistically significant.